2015
DOI: 10.11648/j.edu.20150401.14
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Undergraduate Students about Three Teaching Methods; Lectures, Practical and Problem Based Learning Sessions

Abstract: Abstract:From biochemical education point of view, it is so difficult to make the biochemistry more interesting by adopting one teaching method. The aim of this article is to investigate the perceptions of the undergraduate students of the department of chemistry at king Khalid university about three teaching methods; lectures, practical and problem based learning sessions. A second objective is to compare the students perceptions to their performance in three different exams depending on the information gaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition, research has demonstrated that 78% of students found PBL sessions engaging, and 52.3% found it beneficial for enhancing their knowledge, skills, and critical thinking abilities [59,66,67]. Students in another study reported that their knowledge was more memorable and easily recalled during PBL sessions compared to other instructional methods [68]. Notably, student interest in PBL sessions varies across years, with a gradual increase occurring beginning in the first year (29.7%) and culmination occurring in the final year (70.0%).…”
Section: Problem-based Learningmentioning
confidence: 99%
“…In addition, research has demonstrated that 78% of students found PBL sessions engaging, and 52.3% found it beneficial for enhancing their knowledge, skills, and critical thinking abilities [59,66,67]. Students in another study reported that their knowledge was more memorable and easily recalled during PBL sessions compared to other instructional methods [68]. Notably, student interest in PBL sessions varies across years, with a gradual increase occurring beginning in the first year (29.7%) and culmination occurring in the final year (70.0%).…”
Section: Problem-based Learningmentioning
confidence: 99%